Tongue pyogenic granuloma excision by using ultrasonic scissors - Al- Hadeethi, Yahia F. Hussein; Mohamad, Irfan; Periasami, Chentilnathan (Penerbit USM, 2011)
Pyogenic granuloma develops as a mucosal reaction response to repeated trauma which can be a physical trauma or chronic infection in origin. In the oral cavity, pyogenic granulomas commonly occur on the gingiva owing to presence of chronic irritation by the calculus or foreign material in the gingival sulcus (Akyol et al., 2001). Tongue is relatively less favorable site for this benign lesion. Although the reason is unclear, the lateral part of the tongue has more risk due to its closer anatomical relation to the teeth or dentures (Croton and Kale, 2003). Surgical excision is the most common treatment of these lesions. Various types of techniques and instruments can be used to excise the lesion. The most commonly used are cold steel instruments and diathermy techniques. A newly developed tool, ultrasonic scissors which are used in abdominal and thoracic surgeries can be safely utilized to treat this lesion on the tongue. A case of partial glossectomy using harmonic instrument in Malaysia was recently reported (Irfan et al., 2011). Its use in benign tongue lesion such as pyogenic granuloma is rarely described.